Sustained Release of Chlorhexidine from Modified Titanium Surfaces (In-Vitro Study): Sustained Release of Chlorhexidine from Modified Titanium Surfaces - Parmar, Dr. Mayank; Patel, Dr. Nidhi; Patel, Dr Sapan; Parmar, Dr Mayur; Shah, Dr Foram; Patel, Dr Bhavin (National Journal of Integrated Research in Medicine, 2019)
Background and Aim: Adjunctive antiseptic agent chlorhexidine is often recommended for decontamination in the treatment of peri-implant infections. However, action of chlorhexidine on the titanium surface in the peri-implant environment needs further research. The purpose of present study was to assess chlorhexidine interaction with titanium implant surfaces to estimate its antiplaque efficacy. The purpose of present study was to assess interaction of chlorhexidine with titanium surfaces to estimate its antiplaque potential in the peri-implant environment. Material and Methods: Four modified titanium surfaces were prepared from grade 4 commercially available pure titanium. No surface treatment- control (machined surface, MA), Acid mix of 10% HNO3 and 5% HF (HNF), Hydroxy apatite coated - Resorbable blast media (hydroxyapatite particles cleaned with nitric acid) (HAC), Sandblasting and acid etching (SBAE). Each sample was incubated with phosphate-buffered saline (PBS) or whole saliva for 2 hours. After 1 minute exposure to 0.2 % chlorhexidine gluconate solution, Spectrophotometer was used to measure chlorhexidine release on days 1, 2, and 5. Results: Chlorhexidine exposed titanium surfaces exhibited chlorhexidine release for short duration of time. Chlorhexidine levels dropped rapidly within 3 days time. SBAE and HAC released more chlorhexidine than HNF and MA, specifically in saliva-coated group. Conclusion: This study suggests that titanium surface modifications significantly influence chlorhexidine uptake and release. In the saliva-filled oral cavity, SBAE and HAC shows increased chlorhexidine uptake capacity. The slow chlorhexidine release rate suggests substantivity, which provides a long-term antiplaque effect. [Parmar M Natl J Integr Res Med, 2019; 10(5):75-81]